ANALISIS MANAJEMEN RISIKO KEUANGAN PADA UMKM WARUNG MAKAN “TANJUNG RAYA” DI KOTA SEKADAU - Junianta, Maria; Yulita; Mutyarani, Rara (FEB Universitas Sam Ratulangi Manado, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of local economies in Sekadau City, yet face financial risk management challenges. This study aims to analyze financial risk management at Tanjung Raya Food Stall. Using qualitative methods with descriptive analysis, interviews, and documentation, the results show that Tanjung Raya successfully manages financial risks through: (1) innovative menu and customer service, (2) business diversification (catering), (3) efficient cash flow and inventory management, and (4) independent working capital management. Tanjung Raya demonstrates effective financial risk management, reflecting prudent financial management and a focus on sustainability